UNP SIGAP Logo Design as an Earthquake and Tsunami Disaster - Sari, Dwi Mutia (Journal of Community Research and Service, 2024)
A brand is an intangible asset that summarizes the experience of an entity. The asset value of a well-built brand is very high, it can even exceed all the physical assets of the entity concerned. One of the most important brand building activities is designing a visual identity, such as a logo. A logo is the entrance that reflects a brand. Considering how important a logo is for a brand, it is appropriate that the logo design process is well designed and fulfills the design principles and logo principles. The purpose of this research is to produce a product in the form of a logo and test the feasibility of a logo that meets the design and logo principles. This research uses the Research and Development (R&D) research method, which is used to produce certain products based on its stages so as to produce a feasible product. In the validation test conducted by design and media experts using validation sheets, it shows that the feasibility of the UNP SIGAP logo as one of the visual identities of the UNP visual branding process as an earthquake and tsunami disaster response university meets the "very good" category for the design principle category with a percentage of 92.30% and 94.11% for the logo principle category.